GCTOF-MS and HPLC Identification of Phenolic Compounds with Different Fractional Extracts of Lepironia articulata - Rashidi Othman; Razanah Ramya; NorazianMohd.Hassan; Suhair Kamoona (Journal of Pharmacy and Nutrition Sciences, 2020)
Cyperaceae species have an intrinsic value as a source of active elements with biological activity from the family of monocotyledonous known as sedges. Sedges grow in all types of soils associated with wetlands or poor soils. The aim of this present study is to evaluate the content of phenolic compounds by qualitative and quantitive analysis on Lepironia articulata. Dried leaves of L. articulata were successfully extracted by using water extraction then separated with different solvent polarities; petroleum ether, ethyl acetate and butanol fractions before being analysed using GCTOF-MS, microplate reader and HPLC. The result from the GCTOF-MS analysis of fractional extracts showed that 48 compounds were found in petroleum ether, ethyl acetate and butanol extracts. From those extracts, only six phenolic compounds were identified in ethyl acetate and butanol extracts which were 2-Methoxy-4-vinylphenol, Phenol, 2,4-bis(1,1-dimethylethyl)-, 4-Hydroxybenzaldehyde, Catechol, Phenol, 2-methoxy- and Vanillin. The total phenolic content was found to be 984.63 ± 5.96 μg GAE/g DW in L. articulata. Quantitative analysis of individual phenolic acid by HPLC showed the predominant amount of Vanillic acid (0.48 ± 0.00 μg/g DW) in ethyl acetate while 4-Hydroxybenzoic acid and Caffeic acid, both of which were 0.12 ± 0.00 μg/g DW in butanol extracts. In the present study, the plant extracts demonstrated the highest phenolic compound detected in ethyl acetate and butanol.